Single-Port Fluorescence Immunoassay for Concurrent Quantification of Live and Dead Bacteria: A Strategy Based on Extracellular Nucleases and DNase I - Yuhan Wang; Han Dong; Hang Yu; Shaofeng Yuan; Hideya Kawasaki; Yahui Guo; Weirong Yao (Molecules)
Bacteria are the primary culprits of global foodborne diseases, making bacterial detection one of the most critical aspects of food safety. The quantification of viable and dead bacteria is typically achieved through distinct methodologies, such as culture-based methods and molecular biological techniques. These approaches often have non-overlapping requirements in terms of sample pre-treatment and detection equipment. However, in this presented work, bacterial extracellular nucleases and DNase I were utilized to achieve the simultaneous quantification of both live and dead bacteria in a single well of a microplate. The detection limits of the method for live and dead bacteria are estimated to be 7.13 × 105 CFU/mL and 3.54 × 105 CFU/mL, respectively. In the application of detecting bacteria in pickled pork stewed bamboo shoot soup, the detection limit for live bacteria can be reduced to as low as 102 CFU/mL within 24 h after enrichment cultivation.